CNS infections in patients with hematological or oncological diseases (including cellular therapies): 2024 update of the guideline of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) - Akdas, Rehsan; Schalk, Enrico; Stemler, Jannik; Schwartz, Stefan; Meyding-Lamadé, Uta; Panse, Jens P.; Krüger, William; Rohde, Holger; Ruhnke, Markus; Christopeit, Maximilian; Angstwurm, Klemens; Heußel, Claus Peter; et al. (European journal of cancer, 2026)
Background - Infections of the central nervous system (CNS) occur in up to 15% of patients with hematological or oncological diseases (HOD), particularly in high-risk populations. The most common causative agents are viruses or fungi. Prompt initiation of adequate diagnostic procedures and anti-infective treatment is crucial, as treatment delays increase mortality. - Methods - We present an update of our previous guideline published in 2016 on the management of CNS infections in patients with HOD. The grading of recommendation strength and level of evidence followed the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) standards, based on a systematic literature review and a stepwise consensus process involving experts in internal medicine, hematology, oncology, infectious diseases, neurology, microbiology, and radiology. This process included several web-based meetings by the guideline panel, whereas the final recommendations were approved by the assembly of the Infectious Diseases Working Party of the German Society of Hematology and Medical Oncology in September 2024. - Findings and interpretation - Evidence-based recommendations on the diagnosis and treatment of CNS infections in adult patients with HOD are essential in daily clinical practice to improve outcomes for patients at high risk of morbidity and mortality.